2017
DOI: 10.1016/j.jjcc.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 is associated with macrophage infiltration and polarization in human epicardial adipose tissue in coronary artery disease

Abstract: Findings suggest a link between enhanced netrin-1 expression in EAT and macrophage infiltration and polarization in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Moreover, when we study the distribution of macrophage subtypes, our study shows that only CD11c and CD11c/CD68 ratio (M1-macrophage phenotypes), but not CD206 , were more significantly overexpressed in IHD-T2DM patients when compared to IHD-NDM or control group. In agreement with our findings, Gurses et al [16] observed a shift to pro-inflammatory M1-macrophage phenotype in EAT of patients with coronary artery disease (CAD) compared to the control group (without CAD), reflected by increased of CD11c , CD11c/CD68 and CD11c/CD206 ratios, but not CD206 . According to our results, Hirata et al [17] showed similar results, demonstrated that pro-inflammatory macrophages are more dominant in EAT when compared with and without CAD patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, when we study the distribution of macrophage subtypes, our study shows that only CD11c and CD11c/CD68 ratio (M1-macrophage phenotypes), but not CD206 , were more significantly overexpressed in IHD-T2DM patients when compared to IHD-NDM or control group. In agreement with our findings, Gurses et al [16] observed a shift to pro-inflammatory M1-macrophage phenotype in EAT of patients with coronary artery disease (CAD) compared to the control group (without CAD), reflected by increased of CD11c , CD11c/CD68 and CD11c/CD206 ratios, but not CD206 . According to our results, Hirata et al [17] showed similar results, demonstrated that pro-inflammatory macrophages are more dominant in EAT when compared with and without CAD patients.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to the macrophage infiltration, our work has shown that mRNA expression of CD68 was increased in EAT in patients with IHD and T2DM when compared with patients without T2DM and control group. In this sense, there are studies that have shown an increase in macrophage infiltration in the EAT of CAD patients, reflected by increased CD68 macrophage infiltration [16, 17]. In recent years, several studies have indicated that insulin resistance and T2DM are associated with the inflammation of adipose tissue [4244].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence supporting that the presence and severity of the cardiovascular disease can be detected using certain biomarkers and components of the lipid profile. However, to our knowledge, this is the first study that has reported the association among LCI ≥16, RBP and ACS [14][15][16].…”
Section: Discussionmentioning
confidence: 78%
“…Netrin-1 inactivated macrophage migration and supported chemoattraction of coronary artery smooth muscles. Netrin-1 also strongly reduces leukocyte recruitment into the vascular wall in atherosclerosis, and lack or inhibition of Netrin-1 by proatherogenic factors has shown to increase leukocyte adhesion to the endothelium [ 34 , 74 , 75 ].…”
Section: Netrin and Diabetic Complicationsmentioning
confidence: 99%